The Influence of Health Education on Adolescents Knowledge of Personal Hygiene Zir Bin Hubaisy - Gagas Abdi Pamungkas; Indri Puji Lestari; Rezka Nurvinanda (Genius Journal, 2027)
Introduction: Personal hygiene is an essential aspect of adolescent health because this developmental stage is associated with an increased risk of health problems, including diarrhea, dental caries, skin infections, and other communicable diseases. Proper personal hygiene practices involve maintaining the cleanliness of the hair, scalp, eyes, nose, ears, skin, hands, feet, nails, and genital area. Improving adolescents' knowledge through health education is considered an effective strategy for promoting healthy hygiene behaviors. Objective: This study aimed to determine the effect of health education on adolescents' knowledge of personal hygiene at MTAQ Zir Bin Hubaisy in 2025. Method: This study employed a pre-experimental design using a one-group pretest–posttest approach. A total of 30 adolescents aged 12–14 years were recruited using consecutive sampling. Data were collected using a structured questionnaire to assess participants' knowledge of personal hygiene before and after the health education intervention. Data were analyzed using the appropriate statistical test with a significance level of p < 0.05. Result: The findings demonstrated a significant improvement in adolescents' knowledge of personal hygiene following the health education intervention (p = 0.001), indicating that health education effectively increased participants' knowledge. Conclusion: Health education significantly improves adolescents' knowledge of personal hygiene. Implementing regular health education programs in schools and other educational settings is recommended to enhance adolescents' awareness and promote healthy hygiene practices.